The relationships between cholesterol crystals, NLRP3 inflammasome, and coronary atherosclerotic plaque vulnerability in acute coronary syndrome: An optical coherence tomography study - Xue, Chao; Chen, Qizhi; Bian, Ling; Yin, Zhaofang; Xu, Zuojun; Zhang, Huili; Zhang, Qingyong; Zhang, Junfeng; Wang, Changqian; Du, Run; Fan, Li (Frontiers in Cardiovascular Medicine, 2022)
Background: Cholesterol Crystals (CCs) in lesions are the hallmark of advanced atherosclerotic plaque. Previous studies have demonstrated that CCs could activate NLRP3 inflammasome, which played an important role in atherosclerotic lesion progression. However, the relationship of CCs, NLRP3 inflammasome pathway and plaque vulnerability in ACS patients is still not elucidated. Methods: 269 consecutive acute coronary syndromes (ACS) patients with 269 culprit lesions were included in this study. CCs and other plaque characteristics within the culprit lesion segment were evaluated by optical coherence tomography (OCT) before percutaneous coronary intervention (PCI). The NLRP3 mRNA expression in peripheral blood mononuclear cells (PBMCs), serum levels of interleukin (IL)-1β, IL-18 and other biological indices were measured. Results: CCs were observed in 105 (39%) patients with 105 culprit lesions. There were no significant differences in baseline clinical characteristics between the patients with CCs (CCs group, n=105) and patients without CCs (non-CCs group, n=164) within culprit lesion segment except for lipoprotein(a) (Lp(a)). CCs group had higher level of NLRP3 mRNA expression in PBMCs and higher levels of serum cytokine IL-1β and IL-18. OCT showed that CCs group had longer lesion length, more severe diameter stenosis, and less minimum luminal area (MLA) than non-CCs group (all p<0.05). The frequency of thin-cap fibroatheroma (TCFA), thrombus, macrophages accumulation, plaque rupture, micro channel, calcification, spotty calcification and layered plaque were higher in CCs group than in non-CCs groups (all p<0.05). Multivariate logistic analysis revealed that the level of NLRP3 expression (OR=10.204), IL-1β levels (OR=3.523), IL-18 levels (OR=1.006), TCFA (OR=3.593), layered plaque (OR=5.287), MLA (OR=1.475), macrophage accumulation (OR=2.881) and microchannel (OR=3.185) were independently associated with CCs. Conclusions: ACS patients with CCs in culprit lesion had higher expression of NLRP3, IL-1β, IL-18 and had more vulnerable plaque characteristics than patients without CCs. CCs might have interaction with NLRP3 inflammasome activation in ACS patients, which could contribute to plaque vulnerability in culprit lesion.